The access to justice for vulnerable persons in the Italian judicial system: minors and their participation in family proceedings - Di Salvo, Cettina (2021)
The paper addresses issues concerning the fundamental right of access to justice for vulnerable persons, particularly children, in the Italian legal system. After analyzing the aspects related to effective access to justice in the domestic and European legal framework, the need to ensure the judicial protection of people in vulnerable situations is emphasized through the attenuation of procedural «formalism», the adoption of special measures and procedural rules for the processing of the process, which must be adapted to the peculiarity of the factor causing the fragility. The effective implementation of children’s access to justice includes the right to participate and be heard in civil proceedings that affect their lives and also requires that their views be considered following their levels of maturity and understanding. Finally, the rules governing the hearing of minors are examined.